リョウキョクイキ カラ ミタ チキュウ ナイブ ノ フキンコウ コウゾウ ト ダイナミクス ニ カンスル ケンキュウ シュウカイ ホウコク - 金尾, 政紀; カナオ, マサキ; 臼井, 佑介; ウスイ, ユウスケ; Kanao, Masaki; Usui, Yusuke (2006)
P(論文) 平成18年2月2,3日に国立極地研究所講義室にて,「両極域から視た地球内部の不均質構造とダイナミクスに関する研究集会」が開催された(参加者計32名).極域の固体地球物理科学に関連する研究者が集まり,最新の研究成果の発表と学際的な情報交換を行い,また今後の研究の取り組み方を議論した.第1部(極域から視た地球内部の科学的成果)では,地球中心核・最下部マントル～不部マントル・地殻における様々な地震学的不均質構造とその変動現象(ダイナミクス)に関する発表をはじめ,南極プレート周辺の地震活動,また2004年12月のスマトラ沖巨大地震に関連した研究が紹介された.第2部(極域における将来計画の展望)では,地震波伝搬モデリングなどについての今後導入すべき解析手法,インフラサウンド観測や高サンプリングGPS観測等,極域における様々な時空間スケールでの特徴的な振動現象を解明するための斬新なアイデアが紹介された.2日目は,国際極年2007-2008に関連した観測計画の紹介をはじめ,東ドロンニングモードランドを中心に今後の国際共同研究の具体的な進め方について議論した. A workshop on "Heterogeneous structure and dynamics of the Earth's interior viewed from polar regions" was held on 2nd-3rd February 2006, at the National Institute of Polar Research with 32 participants. The meeting provided the opportunity to exchange valuable information involving solid Earth studies around the polar region, followed by a discussion about future plans. The first section of the workshop covered the present status of scientific results, such as insights of the inner structure and dynamics of the Earth viewed from high latitude. Significant results concerning the heterogeneous structure were demonstrated from the depths ranging from the deep interior of the Earth to the upper mantle and overlying crust. Several remarkable topics concerning the Sumatra Earthquake on December 2004, were also presented involving seismic activity of the Antarctic Plate, free oscillation of the Earth, Tsunami waves, dynamic triggering, and so on. The second section of the workshop treated future plans both for the development of new analytical methods and for observations in the polar regions. Multidisciplinary studies, moreover, were proposed for the Antarctica including high-density super-conducting gravimetric network, infrasonic observations, high sampling GPS recording, ice-quake monitoring, etc. Finally, several international activities in Eastern Dronning Maud Land were discussed with regard to the International Polar Year (IPY) in 2007-2008. departmental bulletin paper